10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
An 8-year-old spayed female domestic shorthair cat presented with anorexia and weight loss. A complete blood count revealed mild nonregenerative anemia, circulating blasts, dysplastic granulocytes, and basophilia. Both feline leukemia virus (FeLV) and feline immunodeficiency virus tested negative upon SNAP testing using peripheral blood and PCR using bone marrow. Bone marrow aspiration revealed an increased number of blast cells and basophils, and some blast cells were positive for MPO staining. Based on the basophilic lineages observed in the peripheral blood and bone marrow, acute myeloid leukemia with maturation (AML-M2) with basophilic differentiation was the most likely diagnosis in this case. This study reports the unique morphologic features of a rare case of AML-M2 with suspected basophilic differentiation in an FeLV-negative cat.